Odpowiedź :
f)
x/2 = 2/5(4 - x) - 4 |·10
10 · x/2 = 10 · 2/5(4 - x) - 4 · 10
5x = 4(4 - x) - 40
5x = 16 - 4x - 40
5x + 4x = -24
9x = -24 /:9
x = -24/9 = - 8/3
x = - 2 i 2/3
g)
(2x - 1)/5 - (x - 2)/2 = 0,7x |·10
10/5 · (2x - 1) - 10/2 · (x - 2) = 10 · 0,7x
2(2x - 1) - 5(x - 2) = 7x
4x - 2 - 5x + 10 = 7x
-x + 8 = 7x
-x - 7x = -8
-8x = -8 /:(-8)
x = 1
Odpowiedź:
f)
x/2 = 2/5 (4 - x) - 4
1/2x = 8/5 - 2/5x - 4
1/2x + 2/5x = 1 3/5 - 4
5/10x + 4/10x = -2 2/5
9/10x = -12/5 /*10/9
x = -12/5 * 10/9 = -8/3 = -2 2/3
g)
(2x-1)/5 - (x-2)/2 = 0,7x
2/5x - 1/5 - 1/2x + 1 = 0,7x
4/10x - 5/10x - 0,7x = -4/5
-0,1x - 0,7x = -0,8
-0,8x = -0,8 /:(-0,8)
x = 1
Szczegółowe wyjaśnienie: